MATHEMATICAL MODELLING OF A MIGRATION PROCESS AND FORECASTING SOLUTIONS FOR A 1-, 2-, 3-LAYER SUBSOIL OF THE AERATION ZONE - Petrova E.V.; Sergeev V.I.; Shimko T.G. (My University, 1996)
A study of the sorption capacity of clay soils sorption capacity regarding heavy metals has made it possible to quantify the procedure for the determination of migration process parameters, and on the basis of them to make a forecast of heavy metals transport throughout the aeration zone of the subsoil with time. The program MASSEX (for IBM-compatible computers) has been developed, and designed for solving prediction problems in 1-, 2- and 3-layer media.